PERAN KETERIKATAN KERJA DALAM MEMEDIASI TRANSFORMASI DIGITAL MSDM TERHADAP KINERJA KARYAWAN UMKM - Lisa Elianti Nasution; Muhammar Syafii; Indah Mawarni (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
This study aims to analyze the role of work engagement in mediating the effect of digital transformation of human resource management (HRM) on employee performance in SMEs in Medan City. This research employs a quantitative approach with an explanatory design. Data were collected through questionnaires distributed to 100 SME employees using purposive sampling technique. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results indicate that digital transformation of HRM has a positive and significant effect on work engagement and employee performance. Work engagement also has a positive and significant effect on employee performance. Furthermore, work engagement significantly mediates the relationship between digital transformation of HRM and employee performance with partial mediation. These findings suggest that the success of digital transformation in improving employee performance depends not only on the implementation of technology but also on the level of employee work engagement. This study contributes theoretically to the development of digital HRM literature and provides practical implications for SMEs in managing human resources more effectively in the digital era.